2023
DOI: 10.1093/mnras/stad3225
|View full text |Cite
|
Sign up to set email alerts
|

ExoMol line lists – LIII: empirical rovibronic spectra of yttrium oxide

Sergei N Yurchenko,
Ryan P Brady,
Jonathan Tennyson
et al.

Abstract: Empirical line lists BRYTS for the open shell molecule 89Y16O (yttrium oxide) and its isotopologues are presented. The line list covers the 6 lowest electronic states: X 2Σ+, A 2Π, A′ 2Δ, B 2Σ+, C 2Π and D 2Σ+ up to 60 000 cm−1 (<0.167 μm) for rotational excitation up to J = 400.5. An ab initio spectroscopic model consisting of potential energy curves (PECs), spin-orbit and electronic angular momentum couplings is refined by fitting to experimentally determined energies of YO, derived from published YO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…This study aims to show the numerical equivalence of the adiabatic and diabatic representations in nuclear motion calculations of rovibronic energies and spectral properties for two selected diatomic systems, represented by two coupled electronic states: yttrium oxide (YO) and carbon monohydride (CH) molecules illustrated in Figure . YO shows avoided crossings between the B 2 Σ + , D 2 Σ + and A 2 Π, C 2 Π states as described by Yurchenko et al YO has broad scientific interest, having been observed in stellar spectra, and found use in solar furnaces , and magneto-optical traps. , YO is a complex system showing many low-lying electronic states; accurate descriptions of its avoided crossings will be valuable to works in several fields. CH is one of the most studied free radicals because it occurs in such a wide variety of environments: it has been observed in flames, , solar and stellar spectra, spectra of comets, ISM, and molecular clouds …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This study aims to show the numerical equivalence of the adiabatic and diabatic representations in nuclear motion calculations of rovibronic energies and spectral properties for two selected diatomic systems, represented by two coupled electronic states: yttrium oxide (YO) and carbon monohydride (CH) molecules illustrated in Figure . YO shows avoided crossings between the B 2 Σ + , D 2 Σ + and A 2 Π, C 2 Π states as described by Yurchenko et al YO has broad scientific interest, having been observed in stellar spectra, and found use in solar furnaces , and magneto-optical traps. , YO is a complex system showing many low-lying electronic states; accurate descriptions of its avoided crossings will be valuable to works in several fields. CH is one of the most studied free radicals because it occurs in such a wide variety of environments: it has been observed in flames, , solar and stellar spectra, spectra of comets, ISM, and molecular clouds …”
Section: Introductionmentioning
confidence: 91%
“…As an example of a two-state system with narrow, coupled-bound electronic curves, we chose the ab initio PEC curves of the B 2 Σ + and D 2 Σ + states of YO from Smirnov et al 90 with the NAC from Yurchenko et al 53 …”
Section: Spectroscopic Modelsmentioning
confidence: 99%